1995
DOI: 10.1093/nar/23.10.1758
|View full text |Cite
|
Sign up to set email alerts
|

Cell stress and translational inhibitors transiently increase the abundance of mammalian SINE transcripts

Abstract: The abundance of Alu RNA is transiently increased by heat shock in human cell lines. This effect is specific to Alu repeats among Pol III transcribed genes, since the abundance of 7SL, 7SK, 5S and U6 RNAs is essentially unaffected by heat shock. The rapid induction of Alu expression precedes the heat shock induction of mRNAs for the ubiquitin and HSP 70 heat shock genes. Heat shock mimetics also transiently induce Alu expression indicating that increased Alu expression is a general cell-stress response. Cycloh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
238
0
3

Year Published

2000
2000
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 280 publications
(250 citation statements)
references
References 40 publications
9
238
0
3
Order By: Relevance
“…Expression of this RNA is increased up to 100-fold in response to environmental stresses such as heat shock (Liu et al 1995;Allen et al 2004). Coimmunoprecipitation and binding experiments have provided evidence that B2 RNA associates with RNA pol II upon heat shock, and in vivo and in vitro transcription experiments have revealed that B2 RNA inhibits RNA pol II by preventing the formation of active preinitiation complexes Espinoza et al 2004).…”
Section: Mouse B2 Rnamentioning
confidence: 99%
“…Expression of this RNA is increased up to 100-fold in response to environmental stresses such as heat shock (Liu et al 1995;Allen et al 2004). Coimmunoprecipitation and binding experiments have provided evidence that B2 RNA associates with RNA pol II upon heat shock, and in vivo and in vitro transcription experiments have revealed that B2 RNA inhibits RNA pol II by preventing the formation of active preinitiation complexes Espinoza et al 2004).…”
Section: Mouse B2 Rnamentioning
confidence: 99%
“…The excess of SRP9/14 over SRP was only observed in immortalized cell lines [12], and the expression levels of SRP9/14, relative to SRP, will have to be investigated in different tissues and under different physiological conditions to better characterize the potential regulation of Alu RNA activity. Moreover, as most of the previous studies concerning Alu RNA transcription were performed using cultured cancer cells [8,9,15,18,19], it would also be interesting to measure the level of Alu RNA in different tissues or in cultured primary cells. It was indeed recently shown that the level of Alu transcripts is much lower in normal than in cancerous hepatic cells [20].…”
Section: Free Alu Rnas and Protein Translationmentioning
confidence: 99%
“…The deviation of SINEs from ancestor RNA in the 3Ј-region should be related either to the retroposition process (e.g., acquiring higher affinity to the reverse transcriptase) or to the control of transcription. Indeed, most of the time transcription of short retroposons is repressed except for special conditions such as early embryogenesis (Bachvarova 1988;Grigoryan et al 1985) or stress (Liu et al 1995;Panning and Smiley 1993).…”
Section: Evolution Of Can Sines and Carnivoresmentioning
confidence: 99%